THE GENERAL PRINCIPLES OF THE FORMATION OF DISTRIBUTIVE RELATIONS IN UKRAINE AT THE MACROECONOMIC LEVEL - Alekseeva, A. Yu. (Science and Transport Progress, 2006)
The article discusses the issues of allocation of profits, and the problem of poverty related thereto. It examines the problem of middle class and is complemented by the analysis of statistical data. Attention is paid to the role of state in the system of profits allocation.